Using anti-Müllerian hormone to predict premature ovarian insufficiency: a retrospective cross-sectional study - Huang, Yuanxin; Kuang, Xiaojun; Jiangzhou, Huiting; Li, Meiling; Yang, Dongjian; Lai, Dongmei (Frontiers in Endocrinology, 2024)
Background Premature ovarian insufficiency/failure (POI/POF) is a significant issue for women of reproductive age. Anti-Müllerian hormone (AMH) is a potential biomarker of ovarian reserve, but its clinical value in diagnosing and predicting POI/POF remains unclear. This study aimed to analyze the correlation between AMH and basal follicle-stimulating hormone (FSH) levels in women aged 18 to 40 and evaluate AMH’s predictive value for POI/POF. Methods A total of 21,143 participants aged 18-40 who visited the gynecology department or underwent physical examinations at the International Peace Maternity and Child Health Hospital in Shanghai, China, from July 2016 to June 2021 were enrolled. Demographic information and laboratory test results were collected, including age, FSH, AMH, E2 and test dates. Participants were grouped by FSH and AMH levels, and subgroup analyses were performed to investigate the relationship between these hormones and age. The AMH level associated with POI risk was evaluated using restricted cubic splines (RCS) and logistic regression. Clinical benefit was assessed by decision curve analysis (DCA). Results Participants with higher FSH levels had significantly lower median AMH levels and vice versa(p<0.001). At AMH ≥ 0.5 ng/mL, FSH levels were normal or slightly elevated with age. At AMH level below 0.5ng/ml,basal FSH increased significantly with age. At FSH <10 IU/L, AMH levels show a trend of rising and then decreasing with age, reaching a peak at approximately 25 years old and gradually decreasing with age. At FSH ≥10 IU/L, AMH levels show a gradual downward trend with age, and at FSH >40 IU/L, AMH levels remain very low to undetectable values. The RCS showed that the risk of POI/POF in the overall population sharply increased until serum AMH reached a low level (below 0.5ng/ml). DCA showed that a low AMH level had good clinical diagnostic utility in predicting POI/POF. Conclusion Our analysis of a large dataset suggests that serum AMH levels are inversely correlated with FSH levels and that AMH is a good predictor of POI until it drops to a low level.